The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1001/jamanetworkopen.2021.3238
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Maternal Caffeine Consumption and Metabolism and Neonatal Anthropometry

Abstract: IMPORTANCE Higher caffeine consumption during pregnancy has been associated with lower birth weight. However, associations of caffeine consumption, based on both plasma concentrations of caffeine and its metabolites, and self-reported caffeinated beverage intake, with multiple measures of neonatal anthropometry, have yet to be examined. OBJECTIVE To evaluate the association between maternal caffeine intake and neonatal anthropometry, testing effect modification by fast or slow caffeine metabolism genotype. DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 45 publications
1
18
1
10
Order By: Relevance
“…We have previously observed similar results for both self-reported and measured caffeine and paraxanthine. 3 Thus, we have good confidence that measured first trimester caffeine and paraxanthine is an adequate proxy for habitual intake on a population level, without the limitations of self-reported intake. 35 A strength of our study is the use of 2 independent cohorts to evaluate associations: a contemporary cohort reflecting modern caffeine consumption trends in the US and a historical cohort with high consumption.…”
Section: Limitations and Strengthsmentioning
confidence: 88%
See 1 more Smart Citation
“…We have previously observed similar results for both self-reported and measured caffeine and paraxanthine. 3 Thus, we have good confidence that measured first trimester caffeine and paraxanthine is an adequate proxy for habitual intake on a population level, without the limitations of self-reported intake. 35 A strength of our study is the use of 2 independent cohorts to evaluate associations: a contemporary cohort reflecting modern caffeine consumption trends in the US and a historical cohort with high consumption.…”
Section: Limitations and Strengthsmentioning
confidence: 88%
“…Maternal caffeine consumption during pregnancy, even in modest amounts (eg, 50 mg or one-half cup of coffee per day), is associated with lower birth weight and higher rates of birth weight below 2500 g. 1,2 These decreases in birth weight were attributed to shorter birth length and less lean tissue mass in the National Institute of Child Health and Human Development (NICHD) Fetal Growth Studies. 3 The potential mechanism is unclear, but caffeine is a neural stimulant not metabolized by the fetus that accumulates in fetal tissue. 4 Given that approximately 8 in 10 US pregnant women consume caffeine, 5 it is important to determine whether in utero caffeine exposure has long-term growth implications in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up in vitro studies in differentiating cardiomyocytes and neuronal rosettes, which are expected to express adenosine receptors ( Headrick et al, 2013 ), were negative at caffeine exposure up to 100 μM, a concentration that is above the expected level in consumers (∼40–80 µM) and provide reassurance that these levels of activity may not be sufficient to adversely affect cardiac or neuronal development, at least in the periods covered by the assays. This conclusion is supported by the available epidemiology data, which suggest that the most sensitive adverse effect associated with oral caffeine exposure in pregnant women is intra-uterine growth retardation, and not specific malformations of the heart and brain ( Gleason et al, 2021 ).…”
Section: Application Of the Ngra Dart Framework To The Caffeine Case ...mentioning
confidence: 69%
“…We followed this framework for two hypothetical exposure scenarios, applying the PBK model approaches to estimate caffeine's internal maternal and foetal exposure, combined with the biological activity characterisation using the NAMS evaluated in the biological coverage section. Caffeine effects during pregnancy have been a topic of debate for many years, but safety agencies around the world agree that a daily consumption of 200 mg is unlikely to lead to significant adverse reproductive and developmental effects (USDA 2015;EFSA, 2015;FDA, 2018;ACOG, 2020;Gleason et al, 2021;James, 2021;NHS, 2020). Here we found that an oral dose below 20 mg/day and a dermal exposure with 0.1% caffeine would result in a maternal BER higher than one implying that this exposure would result in no in vivo biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hoyt et al reported that 82% of pregnant women in the United States consumed caffeine ( 9 ). In another study, the National Institute of Child Health and Human Development (NICHD) reported that 35% of participants consumed coffee and 41% drank soda daily ( 10 ). A safe dose of daily caffeine intake in pregnancy is not more than 200 mg (or two cups) of coffee ( 11 ).…”
Section: Introductionmentioning
confidence: 99%